Molecular analysis of three DNA mismatch repair protein variants in Chinese families with suspected Lynch syndrome - Li, Juyi; Ni, Haichun; Cheng, Peng; Peng, Yujia; Liu, Lei; Wang, Xiangyang; Cheng, Wei; Li, Hengfei; Wang, Xiufang; Zhang, Hongfeng; Hu, Jifa; Deng, Aiping; et al. (Frontiers in Medicine, 2025)
PurposeThis study aimed to examine pathogenic variations in three families clinically diagnosed with suspected Lynch syndrome (LS).MethodsThree probands clinically diagnosed suspected LS were subjected to immunohistochemical analysis of DNA mismatch repair (MMR) protein. Whole-exome sequencing and Sanger sequencing were performed to screen pathogenic variations. I-TASSER and PyMOL were used to analyze changes in the functional domains of mutant proteins.ResultsA known missense variation (GRCh37 chr2:g.47702367G>A, MSH2:NM_000251:c.1963G>A:p.V655I), a known stop-gain variant (GRCh37 chr2:g.47709984G>T, MSH2:NM_000251:c.2701G>T:p.E901X), and a known frameshift insertion variation (GRCh37 chr2:g.48032124 dupA, MSH6:NM_000179:c.3514dupA:p.R1172Kfs*5) in Family 1, Family 2, and Family 3, respectively, were observed. The c.1963G>A variation caused the 655th amino acid of MSH2 to change from valine to isoleucine, and there were no significant changes in both the overall and local protein models in MSH2. Further, the c.2701G>T variation caused the 901st amino acid of MSH2 to change from glutamic acid to a premature stop codon in exon 16, and the deletion of amino-acids 901–934 caused changes in the Domain 5 of MSH2 protein. Furthermore, the c.3514dupA variation caused the 1172nd amino acid of MSH6 to change from arginine to lysine, followed by frameshift, which caused changes in the Domain 5 of MSH6 protein.ConclusionThe missense variation (MSH2:NM_000251:c.1963G>A:p.V655I) and the stop-gain variation (MSH2:NM_000251:c.2701G>T:p.E901X) were considered uncertain significance for LS, and another pathogenic variation (MSH6:NM_000179:c.3514dupA:p.R1172Kfs*5) has been further confirmed.